THE GLORIOUS EFFECT OF GOD’S CREATION THROUGH BADUY PEOPLE - Tony Salurante (Phronesis: Jurnal Teologi dan Misi, 2018)
In this research I try to show that God’s truth is able to teach unbelievers through what is called general grace. Reading Psalm 19 further shows that God is omnipotent and creator who has love. After showing these methods, this article implies and try to connects to Indonesian Context. One example of how the isolated tribes in Indonesia, Baduy, analyzed the writings of King David in this Psalm. On the one hand, their knowledge is so natural and primitive, but on the other hand, their stewardships of environment can demonstrate the practical mission of the church today and teach believers how response in the midst of an increasingly damaged ecology as a Church.